Role of endogenous monomethylated L-arginine (L-NMMA) after subarachnoid hemorrhage. (1st September 2013) - Jung, Carla S; Lange, B; Zimmermann, M; Seifert, Volker
<x xml:space="preserve">Abstract</x> Objectives: Monomethylated L-arginine (L-NMMA) has been proven to be a strong inhibitor of nitric oxide synthase (NOS) and has been used as an exogenous tool in experimental evaluation of cerebrovascular reactivity leading to vasoconstriction. However, L-NMMA is also produced endogenously and belongs, as does asymmetric dimethylated L-arginine (ADMA), to a family of endogenous NOS inhibitors. While ADMA has been associated with cerebral vasospasm (CVS) but not with delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH), no results are available concerning endogenous L-NMMA and SAH. We therefore decided to investigate the role of endogenous L-NMMA with regard to CVS and DCI after SAH. Methods: Retrospective analysis of cerebro-spinal fluid (CSF) and serum of SAH patients and controls was performed by high performance liquid chromatography (HPLC) and chemiluminescence. Delayed CVS was detected by arteriography and cerebral ischemic events by follow-up computed tomography (CT) scans. Results: Cerebro-spinal fluid and serum L-NMMA concentrations neither correlated with CVS nor with NO2− levels (P > 0·05, in both cases). However, endogenous L-NMMA concentrations correlated with cerebral ischemic events and with the size of infarction (cc = 0·459, P = 0·032, 95% CI: 0·046-0·738). Conclusions: This study shows that endogenous L-NMMA is associated with the occurrence of cerebral ischemic events, but seems not to be involved in CVS after SAH. Therefore, endogenous L-NMMA after SAH features intriguing differences compared with previous reports on exogenous L-NMMA and ADMA after SAH.